INDIVIDUAL EDUCATIONAL TRAJECTORIES IN THE EDUCATIONAL PROCESS OF THE UNIVERSITY - Mustafoyeva Munojat Oltibekovna (Web of Journals Publishing, 2025)
The article reveals the content of the concept of individual educational trajectories, analyzes the advantages of introducing individual educational trajectories into the system of higher professional education, substantiates the effectiveness and necessity of introducing individual educational trajectories into the educational process of the university.
Keywords: Modernization of education, continuous education, individual educational trajectories, design of individual educational trajectories.